GENETIC VARIATION FOR YIELD TRAITS IN MAGIC INDICA PLUS POPULATION AND INDIAN RICE GERMPLASM - T. RAMESH; S.A.HUSSAIN, SANII LANAH, S.VANISRI, SREEDHAR MULINTI R. ABDUL FIYAZ, CH.V DURGA RANI (The Journal of Research, PJTSAU, 2020)
Genetic diversity represents the heritable variation within and between populations of accessions. The success of plant breeding depends on the available genetic variability both indigenous as well as exotic to cater to the need of various farming situations of rice. Higher grain production is the primary trait targeted for the improvement of rice productivity in both favourable and unfavourable environments from its present level. Knowledge of the genetic architecture of genotypes is necessary to formulate efficient breeding methodology. It is essential to find out the relative magnitude of additive and non additive genetic variances, heritability, and genetic gain about the characters of concern to the breeder. The crop improvement program generally involves generation of genetic variability, selection, and yield evaluation trails to evolve promising varieties. The large spectrum of genetic variability in segregating populations depends on the level of genetic diversity among genotypes that are chosen for hybridisation. Besides, heritability and genetic advance are other important selection parameters. The evaluation of heritability helps the plant breeder in determining the character for which selection would be rewarding. The breeders are interested in the selection of superior genotypes based on their phenotypic expression. The major function of heritability estimates is to provide information on the transmission of characters from the parents to the progeny. Heritability estimates along with genetic advance are normally helpful in predicting the gain under selection than heritability estimates alone. Keeping in view the importance of the subject, an attempt was made to estimate genetic variability in rice MAGIC indica plus lines along with rice accessions and four checks.